2016
DOI: 10.1016/j.jglr.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Eurytemora carolleeae in the Laurentian Great Lakes revealed by phylogenetic and morphological analysis

Abstract: In the Laurentian Great Lakes, specimens of Eurytemora have been reported as E. affinis since its invasion in the late 1950s. During an intensive collection of aquatic invertebrates for morphological and molecular identification in Western Lake Erie in 2012-2013, several specimens of Eurytemora were collected. Analysis of these specimens identified them as the recently described species E. carolleeae Alekseev and Souissi 2011. This result led us to assess E. carolleeae's identifying features, geographic distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The DNA was purified from the tissue samples using DNeasy Blood and Tissue Kits (Qiagen, Hilden, Germany), as in previous studies from our laboratory (Vasquez et al. ). Briefly, small (~25‐mg) pieces cut from the tissue samples were placed in 180 μL of Buffer ATL (catalog number, 19076; Qiagen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA was purified from the tissue samples using DNeasy Blood and Tissue Kits (Qiagen, Hilden, Germany), as in previous studies from our laboratory (Vasquez et al. ). Briefly, small (~25‐mg) pieces cut from the tissue samples were placed in 180 μL of Buffer ATL (catalog number, 19076; Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…Amplification of all DNA samples was done using a standard PCR protocol described by Vasquez et al. (), but with annealing temperatures adjusted to the specific primer set. The annealing temperatures varied among experiments based on the predicted annealing temperatures provided by Primer 3, and in some experiments we tried other temperatures to increase (or decrease) the specificity of primer annealing.…”
Section: Methodsmentioning
confidence: 99%
“…One clade mainly inhabits the inner reaches of the estuary and has invaded the Great Lakes (Winkler et al, 2008;Favier and Winkler, 2014), and has been reported as epi-benthic in the lakes (Torke, 2001). The clade in the Great Lakes have been classified as E. carolleeae by Vasquez et al (2016). The other clade in St. Lawrence is mainly found in the middle parts of the estuary, suggesting that it occupies the pelagic habitat (Winkler et al, 2008;Favier and Winkler, 2014).…”
Section: Common Gardening Experimentsmentioning
confidence: 99%
“…The morphological traits used to discriminate between E. affinis and E. carolleeae are nonadaptive (Alekseev and Souissi, 2011;Sukhikh et al, 2013;Lajus et al, 2015), and thus unlikely to have any ecosystem effects (Matthews et al, 2011a). Furthermore, taxonomic classification based on morphology alone is not distinct because some key traits overlap between the two species (Sukhikh et al, 2013;Vasquez et al, 2016) and differentiate between E. affinis populations (Sukhikh et al, 2016). Therefore, we use the E. affinis species name throughout and refer to the E. affinis species complex in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…The species complex has spread multiple times independently from brackish water to freshwater, and established clades in different parts of the world due to its ability to adapt locally (Dodson et al, 2010). There are at least six recognized clades of E. affinis; one clade in Asia, one in Europe, and four in America (Lee, 2000), with recent studies indicating that North American clades represent a separate species (E. carolleeae; Alekseev and Souissi, 2011;Vasquez et al, 2016). Eurytemora in Lake Michigan waters is most common between July and November, being rare in winter and spring (Torke, 2001).…”
Section: Study Speciesmentioning
confidence: 99%